2014
DOI: 10.1590/abd1806-4841.20142516
|View full text |Cite
|
Sign up to set email alerts
|

Bullous pemphigoid and comorbidities: a case-control study in Portuguese patients

Abstract: BACKGROUNDaAlthough rare, bullous pemphigoid (BP) is the most common autoimmune blistering disease. Recent studies have shown that patients with bullous pemphigoid are more likely to have neurological and psychiatric diseases, particularly prior to the diagnosis of bullous pemphigoid.OBJECTIVEThe aims were: (i) to evaluate the demographic and clinical features of bullous pemphigoid from a database of patients at a Portuguese university hospital and (ii) to compare the prevalence of comorbid conditions before t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
77
2
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(106 citation statements)
references
References 24 publications
17
77
2
10
Order By: Relevance
“…The control group consisted of an equal number of healthy individuals (33 females and 24 males), aged 38-81 (mean 60.66± 11.26). No statistically significant (NS) difference between patients and controls was documented in terms of age (t=0.45, p>0.05, NS) and sex (x 2 =0.14, p>0.05, NS).…”
Section: Resultsmentioning
confidence: 80%
“…The control group consisted of an equal number of healthy individuals (33 females and 24 males), aged 38-81 (mean 60.66± 11.26). No statistically significant (NS) difference between patients and controls was documented in terms of age (t=0.45, p>0.05, NS) and sex (x 2 =0.14, p>0.05, NS).…”
Section: Resultsmentioning
confidence: 80%
“…It has been reported that BP patients are more likely than the general population to have schizophrenia before their BP diagnosis7, and unipolar and bipolar disorders are also associated with BP11. On the contrary, another study found no connection between BP and depression12 and none of these studies have reported whether the risk for psychiatric disorders is elevated after the diagnosis of BP.…”
mentioning
confidence: 98%
“…6 A incidência de PB está estimada em dois a 14 novos casos por milhão, sem predominância por género. 7 Manifesta-se através de uma erupção cutânea polimórfica, tipicamente constituída por bolhas subepidérmicas tensas, que podem ter distribuição localizada ou generalizada. O envolvimento das mucosas é pouco comum, estando descrito em cerca de 10 a 25% dos casos.…”
Section: Discussionunclassified
“…: aspirina, captopril, furosemida, penicilina) e a presença de comorbilidades como síndromes linfoproliferativas, diabetes mellitus e doenças neurodegenerativas. 5,7 A relação causal entre as doenças do foro neurológico e a ocorrência de penfigoide bolhoso tem sido muito investigada nos últimos anos. [1][2][3][4][5]7 Embora a sua patogénese ainda não esteja totalmente esclarecida, acredita-se que os processos neurodegenerativos possam predispor o desenvolvimento de PB, através da ativação de mecanismos autoimunes, que produzem autoanticorpos contra antigénios presentes nas células cutâneas e do sistema nervoso central.…”
Section: Discussionunclassified
See 1 more Smart Citation